Spatial Data Integration and Validation for Peatland Fire Risk Mapping in Ogan Ilir District, South Sumatra Province - Sutopo; Saputra, Agus Dwi; Irfan, Muhammad; Mardiansyah, Wijaya; Iskandar, Iskhaq (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
This study aims to map peatland fire vulnerability in Ogan Ilir District, South Sumatra, using a GIS-based spatial data integration approach. The analysis integrates biophysical factors, including soil type, land cover, topography, and rainfall, with anthropogenic variables such as accessibility to roads, settlements, and rivers. A multi-criteria scoring and weighting method was applied to generate the vulnerability map, which was validated using hotspot data from 2019 to 2024. Previous studies in Ogan Ilir primarily focused on fire-potential mapping using simple scoring and overlay techniques without standardized validation. To address this limitation, this study adopts the official methodology outlined in Technical Guidelines No. P.6/PSKL/SET/KUM.1/5/2020 issued by the Ministry of Environment and Forestry and incorporates fire spot data from the Regional Disaster Management Agency (BPBD) for validation. Results show that high-vulnerability areas (Score 3–4) dominate the district, covering 222,855.3 hectares or 90.7% of the total mapped area. Validation indicates that 83.8% of actual hotspots occur within these zones, supported by a kappa accuracy value of 0.8628, reflecting strong model reliability. Key factors influencing vulnerability include land cover dominated by shrubs, swamps, and plantations such as oil palm and rubber; the predominance of Hemic Organosol soils; and low rainfall, especially in southern areas. These findings align with studies across Sumatra highlighting the influence of drained vegetation, accessibility, and human activities on peatland fire susceptibility. Overall, this study provides essential spatial information to support targeted peatland fire mitigation, including enhanced monitoring, strict no-burn policies, and improved water-management practices to maintain sustainable peat moisture.